Perilaku bertelur dan pemilihan habitat bertelur oleh capung jarum Pseudagrion pruinosum (Burmeister) (Odonata: Coenagrionidae) - Uci Sugiman; Helmi Romdhoni; Alexander Kurniawan Sariyanto Putera; Rusnia J Robo; Fenny Oktavia; Rika Raffiudin (Jurnal Entomologi Indonesia, 2019)
Pseudagrion pruinosum (Burmeister) is a common damselfly that is widely distributed in Southeast Asia. However, information related to the oviposition behavior and habitat is still limited. This study was aimed to determine the behavior of P. pruinosum when laying eggs and characterized the oviposition habitat. This research used focal sampling method to observe oviposition behavior and measure habitat parameters on egg-laying location. Results showed, there was mate guarding when P. pruinosum females lay eggs. The male forms a tandem formation (contact mate guarding), then released the female and keep a guarding behavior around the female (noncontact mate guarding). Eggs were placed by the female on plant tissue with the technique of positioning the body to remain on the surface and then submerged. There is no tendency of P. pruinosum behavior towards one type or technique. Based on the results of principal component analysis, 75.8% of habitat components can be described for egg-laying habitat. Air temperature, pH, light intensity, and heterogeneity of vegetation positively correlated with the occurrence of egg-laying while TDS, humidity, water depth, and water temperature were negatively correlated. The results of this study concluded that the characteristics of egg-laying techniques included, i.e contact and noncontact mate guarding by the males and females putting eggs on the surface then submerged into water.